NYERI KEPALA PADA USIA TUA - Hasmawaty Basyir* (NEURONA, 2012)
THERE IS MORE CASE OF SECONDARY HEADACHE IN ELDERLY PATIENT THEREFORE WE NEED TO DO MORE ANAMNESIS LABORATORY TEST AND NEUROIMAGING BECAUSE OF DIFFERENT PHYSIOLOGY DISEASE COMMORBIDITY AND POLYPHARMACY IN ELDERLY PATIENT IT NEEDS DIFFERENT THERAPY FOR SECONDARY HEADACHE IN ELDERLY PATIENT TYPES OF HEADACHE THAT USUALLY HAPPEN IN ELDERLY ARE TENSION TYPE HEADACHE HYPNIC HEADACHE TEMPORAL ARTERITIS SUBDURAL HEMATOMA TRIGEMINAL NEURALGIA POSTHERPETIC NEURALGIA HYPERTENSION SLEEP APNEA ENDOCRINE ABNORMALITIES INFECTION OF THE HEAD AND DRUGINDUCED HEADACHE VASODILATOR ETC